ADQUIRIENDO EXPERIENCIAS Y NUEVOS DESAFIOS - Mauricio Pachas, Pablo (2007)
In the present study the formation of professionals in economy stands out, administration and businesses in the Universities of recognized international prestige; with regard to the invitation by the Department of State of the United States. Such experiences raise challenges for the University Publishes of our Country in the formation of the new professional of economy, administration and businesses, that respond to the context of changes and to the high competitiveness of the markets; where they come emphasizing the countries from Asia and India with his innovation and creativity. Whose intention will be to fortify to the enterprise sector dedicated to the foreign trade, that in the last 5 years has come generating important balances in the trade balance for the benefit from the country. The University must contribute professionals involved in the company and the economic reality, to fortify the potentialities of the regions that dedicate their production to the nontraditional exports and to the development of the Country.